Brief Report on PROSPER Academic Outcomes: Extended Model of Crossover Effects on Young Adult College Success. Issue 6 (7th November 2019) - Spoth, Richard; Trudeau, Linda; Redmond, Cleve; Shin, Chungyeol; Feinberg, Mark E.; Greenberg, Mark T.
Abstract : This study examines crossover effects of adolescent substance misuse preventive interventions on academic success in college. It evaluates pathways of influence on college grades, via effects on school engagement, problem‐solving skills, and substance misuse in high school. Data were collected as part of an Randomized Controlled Trial (RCT) evaluating a multicomponent intervention conducted in 28 school districts with middle school students. At age 19, study participants ( N  = 1, 488) enrolled in college reported on college grades. The model fit the data, supporting hypothesized pathways of intervention impacts. Inclusion of a significant direct effect on college grades further improved model fit. Results support the potential for universal substance misuse preventive interventions delivered by community partnerships during middle school to yield effects on long‐term academic success.